Overexpression of native IF1 downregulates glucose-stimulated insulin secretion by pancreatic INS-1E cells - Kahancová, Anežka; Sklenář, Filip; Ježek, Petr; Dlasková, Andrea (Scientific reports, 2020)
We have previously reported that transient knock-down of ATPase inhibitory factor 1 (IF1) by siRNA upregulates ATP levels and subsequently augments insulin secretion in model pancreatic β-cells INS-1E. Here we investigated how long-term IF1-overexpression impacts pancreatic β-cell bioenergetics and insulin secretion. We generated INS-1E cell line stably overexpressing native IF1. We revealed that IF1 overexpression leads to a substantial decrease in ATP levels and reduced glucose-stimulated insulin secretion. A decrease in total cellular ATP content was also reflected in decreased free ATP cytosolic and mitochondrial levels, as monitored with ATeam biosensor. Consistently, cellular respiration of IF1-overexpressing cells was decreased. 3D structured illumination microscopy (SIM) revealed a higher amount of insulin granules with higher volume in IF1-overexpressing cells. Similar effects occurred when cells were incubated at low glucose concentrations. Noteworthy, activation of PKA by dibutyryl cAMP entirely abolished the inhibitory effect of IF1 overexpression on ATP production and insulin secretion. Mitochondrial network morphology and cristae ultrastructure in INS-1E overexpressing IF1 remained mostly unchanged. Finally, we show that INS-1E cells decrease their IF1 protein levels relative to ATP synthase α-subunit in response to increased glucose. In conclusion, IF1 actively downregulates INS-1E cellular metabolism and reduces their ability to secrete insulin.
Keywords: buněčné linie; RNA, Small Interfering; glukosa; Glucose; upregulace; protein inhibující ATPasu; beta-buňky; Cell Line; krysa rodu Rattus; Down-Regulation; Signal Transduction; Cyclic AMP-Dependent Protein Kinases; down regulace; adenosintrifosfát; ATPase Inhibitory Protein; signální transdukce; proteiny; Insulin-Secreting Cells; zvířata; proteinkinasy závislé na cyklickém AMP; CMP cyklický; malá interferující RNA; sekrece inzulinu; Rats; Animals; Proteins; Insulin Secretion; Adenosine Triphosphate; Up-Regulation; Cyclic CMP